Study on social power and knowledge sharing behavior / Farah Syazreena Azmi and Norfadzilah Abdul Razak - Azmi, Farah Syazreena; Abdul Razak, Norfadzilah (2019)
Knowledge sharing behavior is subjective to an individual. An individual willing to share rely on their decision either to share or not to share with others. One of the factor that influence individual decision is social power. There are four basis of social power which are legitimate, coercive, referent and expertise power. This study aimed to investigate significant relationship between social power and willingness to share knowledge. A survey was conducted among 150 of knowledge workers as in ICT industries which mainly located in Cyberjaya, Malaysia. The data further analysed using Partial Least Square. The attention of this paper concentrated to the finding that social power did not support on an individual decision as to share knowledge. This implies to a leaders practice in organization in order to create and promote knowledge sharing culture.